2013
DOI: 10.1007/s10965-013-0091-y
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked blends of poly(lactic acid) and polyacrylates: AFM, DSC and XRD studies

Abstract: The blends based on poly(lactic acid), (PLA) and polyacrylates (1:1 weight ratio) have been prepared by photopolymerization of three different multifunctional acrylate monomers (pentaerythritol triacrylate, pentaerythritol tetraacrylate and dipentaerythritol pentaacrylate) in matrix of linear PLA. The structure of these systems has been studied by Atomic Force Microscopy (AFM), Differential Scanning Calorimetry (DSC) and X-ray Diffraction (XRD). It was found that the blends are highly crosslinked, rough, heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 28 publications
(33 reference statements)
6
23
0
Order By: Relevance
“…The diffractograms showed that both 3D tubular scaffolds have a signal with the same value as a broadband characteristic of an amorphous peak that increased significantly in comparison with the PLA filament with a lower intensity. These results are in concordance with different studies that reported that PLA is amorphous and depends on the crosslinking of dopants or printed parameters [26][27][28][29].…”
Section: Structural Characterizationsupporting
confidence: 93%
“…The diffractograms showed that both 3D tubular scaffolds have a signal with the same value as a broadband characteristic of an amorphous peak that increased significantly in comparison with the PLA filament with a lower intensity. These results are in concordance with different studies that reported that PLA is amorphous and depends on the crosslinking of dopants or printed parameters [26][27][28][29].…”
Section: Structural Characterizationsupporting
confidence: 93%
“…Scaffold specimens were prepared as 6 mm diameter discs (using a puncture), sterilised (88% CO 2 and 12% ethylene oxide at 45 °C with 180 kPa and 55% of humidity for 10 h) and preserved in a desiccator. to their amorphous state and low concentration at the scaffold surface [36].…”
Section: Characterisation Of Wet-spun Fibre Mesh Scaffoldsmentioning
confidence: 99%
“…specified two PLA diffraction peaks at 2θ = 16.4 and 22.6°, respectively. High temperature processing that led to molecule deformation could be the reason for the low crystallinity apart from the rapid cooling that prevent the PLA chains to organize into crystalline lamella with shortened duration …”
Section: Resultsmentioning
confidence: 99%